Is Anzac Day an incidence of 'Displaced Christianity'?. (October 2015) - Billings, Bradly S.
The experience of the First World War has left a large and indelible mark on Australians and New Zealanders. Whilst the language and associated instruments of Empire, so important at the time of the events a century ago, have largely disappeared from popular life and culture, and the religious form in which it was embedded, that of Christianity together with the social construct of Christendom, is in rapid decline, the metanarrative of Anzac and the associated rituals not only remain, but have only increased and enhanced their place of importance in the context of national life. Drawing on the conceptual language of a 'displaced Christianity' (Northrop Frye), together with the notion of the 'numinous' (Rudolf Otto), this article seeks to explain, and interpret, the cultural phenomenon of Anzac as a worldview embedded in a ritual capable of bringing us into contact with a narrative that both invokes and conveys a sense of meaning and purpose, and invites identification with something that is both wholly greater to and wholly other than ourselves.